Hydrogel fracture experiment: from different stimuli to delayed fratured study (A) - Yip, Zi Hao (Nanyang Technological University, 2023)
Polyacrylamide (PAAm) hydrogel is viewed as a material with immense research potential and market value. PAAm hydrogel has been used in multiple applications that ranges from medicinal field, water and oil treatment, and agriculture purposes. More importantly, it was also nominated as the model material to conduct fracture studies on hydrogel. In this report, dynamic fracture was the mode of fracture selected for the study. While previous studies may have conducted various analysis on dynamic fracture, they have yet to base the research on a material of such significance. Thus, this project would focus on investigating the dynamic fracture properties of PAAm hydrogel and exploring, the relationship between the crack tip velocity and the different pre-stretched conditions. In addition, a proposed crack tip velocity tracking algorithm, using MATLAB image processing toolbox, will be developed to facilitate the project analysis.